Fabrication of Thermally Stable Silver–Organic Complex (TS‐SOC) Based Conductible Filament Materials for 3D Printing. Issue 9 (4th July 2017) - Kim, Tae Yun; Kim, Sang Il; Park, Jong‐Jin
Abstract : Conductive 3D printing has the potential to easily customize parts in the electronics manufacturing industry, by minimizing the contents of conductive fillers. Here, 3D printable filament material with less than 3 wt% of preconductive fillers by forming silver–organic complex (SOC) is achieved. Thermally stable (TS)‐SOC with chelating agents is constructed, and thermal degradation is minimized to 0.91 wt%, even at high temperature under extrusion and 3D printing by the cage effect. In addition, a compact extruder, which has a short (3 cm) heating period, is directly designed, and applied to TS‐SOC‐based filament fabrication to minimize thermal degradation. Also, silver nanoparticles (SNPs) (diameter = 70–90 nm) are uniformly formed by dechelating and chemical reduction of the surface, and form dense conductive percolation networks. Finally, not only are electrical characteristics of a maximum 55.71 S cm −1 obtained, but the intrinsic short‐circuits from nozzle clogging problems of conventional conductive filament could be overcome. Abstract : Thermally stable silver–organic complex‐based conductible filament is demonstrated by highly dispersed preconductive fillers and thermal stability at extrusion and 3D printing temperature for facilitate continuous 3D printing. This process can be cost‐effective with the use of a minimal amount of fillers, and makes it possible to produce customized 3D electrodes with organic silver nanoparticles.